Mediation criteria for interactive serious games aimed at improving learning in children with attention deficit hyperactivity disorder (ADHD) - Teresa Coma-Rosellé; Ana Cristina Blasco-Serrano; María Ángeles Garrido Laparte; Antonio Aguelo Arguis (The Asia-Pacific Society for Computers in Education (APSCE), 2020)
Abstract The PASS intelligence theory (Planning, Attention-Arousal, Simultaneous and Successive) was used together with Feuerstein's mediation model to develop a system of categories for mediation in educational games. This system was used to analyze and improve the design of interactive games that can enhance mediation in learning, particularly in children with attention deficit hyperactivity disorder (ADHD). To this end, interactive games designed for a tabletop device were evaluated within an educational context. 27 children (3-14 years old), who had been diagnosed with ADHD, took part. The tabletop has an intuitive system that allows children to interact directly with objects with which they are familiar, providing opportunities for play and communication. These games were evaluated by the participant observation of individual and group playing experiences, interviews, and two focus groups. The results show that mediation recommendations can be useful in the design of the games. They also confirm the need to improve the adaptability of the games to enable children with ADHD to mediate, plan, and focus their attention. With the aid of a facilitator, the mediating function of learning-games can therefore be applied in the development of the executive functions that are key to learning.